2020
DOI: 10.3390/jcm9020414
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events after Community-Acquired Pneumonia: A Global Perspective with Systematic Review and Meta-Analysis of Observational Studies

Abstract: Acute cardiovascular disease after community-acquired pneumonia is a well-accepted complication for which definitive treatment strategies are lacking. These complications share some common features but have distinct diagnostic and treatment approaches. We therefore undertook an updated systematic review and meta-analysis of observational studies reporting the incidence of overall complications, acute coronary syndromes, new or worsening heart failure, new or worsening arrhythmias and acute stroke, as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 104 publications
5
41
1
Order By: Relevance
“…Previous studies have indicated that cardiovascular events following pneumonia may increase the risk of mortality [35][36][37][38][39][40][41], which explained our findings from the point view of pathophysiological mechanisms. One potential mechanism underlying the association between pneumonia and cardiovascular events is inflammation [38].…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have indicated that cardiovascular events following pneumonia may increase the risk of mortality [35][36][37][38][39][40][41], which explained our findings from the point view of pathophysiological mechanisms. One potential mechanism underlying the association between pneumonia and cardiovascular events is inflammation [38].…”
Section: Discussionsupporting
confidence: 67%
“…Neurological manifestations including acute cerebrovascular diseases (5.7%), were found more in patients with severe condition with COVID-19 as reported Mao et al [27]. A meta-analysis of observational studies from Tralhao et al [28] reported that the incidence of acute stroke was 0.71% in pooled inpatients. Avula et al [29] reported a series of four COVID-19 patients with acute stroke as a presenting symptom.…”
Section: Cerebrovascular Co-morbiditiesmentioning
confidence: 73%
“…A recent systematic review and meta-analysis reported an increased risk of myocardial infarction, heart failure, dysrhythmias and stroke after CAP, which is maximal in the acute phase but persists long-term after resolution of the pneumonia . 23 The finding that there is an increased likelihood of mortality following an episode of hospitalised CAP is reflected by a study in Dutch adults which suggested long-term mortality was higher in those with an underlying comorbidity following an episode of IPD or pneumonia. 24 A possible explanation for this is that an episode of hospitalised CAP can compromise the long-term health status of patients with underlying comorbidities.…”
Section: Discussionmentioning
confidence: 99%